Analysis of the Quality of Teachers' Beliefs in English Language Teaching and Its Implementation in the Independent Curriculum - Annisah Annisah; Sholihin Sholihin; Waliyudin Waliyudin (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2023)
This research aims to reveal the quality of teachers' beliefs in teaching English and its implementation in the curriculum in Bima Regency. The method used is descriptive qualitative and uses purposive sampling techniques. Data was obtained through in-depth interviews with ten teachers from two different schools with questions about teacher experience, teaching experience, educational principles, and teacher personality, then analyzed by data reduction, display, conclusions, and verification. The research results show that: 1) the teacher has an educational background relevant to English subjects and strong motivation to choose an English education major. They also identify idols or role models in learning English. 2) The teachers' teaching experience, with most teachers having taught for more than five years, shows that they consider their main task to be educating, guiding, and providing information to students. Teachers also feel the most impressive experience is when their students succeed. 3) teachers remember the importance of knowledge about content, pedagogy, and students in the teaching process. 4) there is a lack of research and use of specific teaching methods, strategies, and approaches. 5) Implementing the new independent curriculum begins in classes X and XI, with efforts to measure student characteristics and potential, although teachers are still limited in designing open modules. This research concludes that teachers have strong confidence in teaching English, but there are still challenges in implementing the new curriculum.